NADH-fluorescence absorption correction to determine absolute fluorophore concentrations of a liquid tissue model - Braun, Frank; Gretz, Norbert (Measurement science and technology, 2018)
Fluorescence emission intensity is an important indicator for characterising tissue. This study extends our previous work and presents an algorithm to determine the absolute nicotinamide adenine dinucleotide hydrate (NADH) concentration of a liquid tissue model with the aid of a multispectral needle probe. Besides the scattering correction, this newly developed algorithm has the ability to compensate the absorbance effects of the tissue model. As an absorber new coccine (NC) is used to mimic the haemoglobin’s absorbance of human tissue, while Calcilit imitates the tissue’s scattering. The algorithm’s bases are the differences between two definite integrals of the absorbance remission and the fluorescence emission spectrum, respectively. Using this simple mathematic model, an algorithm to determine NADH concentrations between 0.5 and 2.0 mM at 2.7 wt% Calcilit and NC concentrations between 0.252 and 2.520 mM is successfully tested. This results in a mean absolute percentage error (MAPE) of 0.3% for the calculation of the Calcilit concentration and MAPEs of 3.3 and 5.0% to determine the fluorophore concentration.